2018
DOI: 10.1111/idj.12390
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic factors associated with oral health in 12-year-old adolescents: hygiene behaviours and health appointments. A cross-sectional national study in Portugal

Abstract: Our results are in agreement with the literature; the oral health behaviours of 12-year-old Portuguese adolescents can be regarded as satisfactory, although there are important variations across different subpopulations. The influence of sociodemographic factors suggests that tailored strategies must be developed for specific subpopulations, at both individual and community levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…1 study by Santos et al, published in 2019, reported the results of a survey on oral hygiene habits in Portugal that found that women generally brush their teeth more frequently than men . Poor oral health was found to be strongly related to male gender also in 12‐year‐old adolescents . The worse attitude to oral hygiene of males was reported also in other studies that examined populations of different ethnicity …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…1 study by Santos et al, published in 2019, reported the results of a survey on oral hygiene habits in Portugal that found that women generally brush their teeth more frequently than men . Poor oral health was found to be strongly related to male gender also in 12‐year‐old adolescents . The worse attitude to oral hygiene of males was reported also in other studies that examined populations of different ethnicity …”
Section: Discussionsupporting
confidence: 70%
“…19 Poor oral health was found to be strongly related to male gender also in 12-year-old adolescents. 20 The worse attitude to oral hygiene of males was reported also in other studies that examined populations of different ethnicity. 21,22 A number of limitations of the present study should be taken in consideration.…”
Section: Discussionsupporting
confidence: 52%
“…1,[3][4][5][6][7] Inequalities in oral health are deep-rooted, and affect the general health and quality of life of millions of people throughout the world. 8 Studies have shown that families with a low socioeconomic status tend to adopt inadequate health behaviors (such as unfavorable hygiene practices and dietary habits), and have less access to healthcare services and information on oral healthcare, [9][10][11][12][13] thus favoring the onset and progression of dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence represents a period of transition when children are establishing autonomy over their behaviors (16). Additionally, it is a stage when teens do not always appreciate help from adults, despite the strong influence of the family on hygiene issues (17). In 2011, Miko et al examined personal and household hygiene among 299 undergraduate college students In New York.…”
Section: Discussionmentioning
confidence: 99%